806 Do Robotic Procedures Have Improved Perioperative Outcomes After a Learning Curve Period?. (1st April 2022) - Passias, Peter G.; Krol, Oscar; Ahmad, Salman; Passfall, Lara; Kummer, Nicholas; Imbo, Bailey; Tretiakov, Peter S.; Joujon-Roche, Rachel; Moattari, Kevin; Williamson, Tyler; Vira, Shaleen
Abstract : INTRODUCTION: Robot-assisted surgical techniques are being increasingly implemented to increase surgeon accuracy and stamina; however, the effects of surgeon learning curve on outcomes have not been well studied. METHODS: Robotic cases were isolated from single center multi surgeon database. Single surgeon cases were ranked by DOS into 3 quartiles. 1st Quartile (Group I) was analyzed against the 3rd Quartile (Group II). Univariate analysis was used to assess differences between quartiles. A propensity score matched (PSM) cohort of patients undergoing identical surgical procedures was included as a control group. RESULTS: 281 patients undergoing robotic surgery met inclusion criteria (Age: 56±12.5, BMI: 30±6, 42% female) with an average of 1.6 levels fused. Group I had 95 patients and Group II had 94. Group II had a lower EBL (314 vs 492, p<0.05), shorter LOS (3.8 vs 4.7, p=.1), greater amount of levels fused (2 vs 1.4, p=.021), greater amount of decompressions (2.5 vs 1, p=.003), with less return to the OR within 30 days (7% vs 14%, p=.2), and a lower rate of overall post-operative complications (34% vs 54%, p=.04). In a PSM cohort, the mean EBL was 411±790, LOS 3.7±2.7, overall post-operative complication rate 58%, and rate to return to OR within 30 days was 8%. CONCLUSIONS: There is a substantial learning curve that exists in order to capture the potential benefits of robotic surgery. Performing more robotic cases over time can potentially result in a surgeon lowering length of stay, EBL, and complication rate. Furthermore, this study shows that progressing through this learning curve allows a surgeon to become more comfortable performing larger surgeries in the form of greater levels of decompression.